Calcium‐Ion Binding Mediates the Reversible Interconversion of Cis and Trans Peroxido Dicopper Cores. (29th July 2021) - Vargo, Natasha P.; Harland, Jill B.; Musselman, Bradley W.; Lehnert, Nicolai; Ertem, Mehmed Z.; Robinson, Jerome R.
Abstract: Coupled dinuclear copper oxygen cores (Cu2 O2 ) featured in type III copper proteins (hemocyanin, tyrosinase, catechol oxidase) are vital for O2 transport and substrate oxidation in many organisms. μ ‐1, 2‐ cis peroxido dicopper cores ( C P ) have been proposed as key structures in the early stages of O2 binding in these proteins; their reversible isomerization to other Cu2 O2 cores are directly relevant to enzyme function. Despite the relevance of such species to type III copper proteins and the broader interest in the properties and reactivity of bimetallic C P cores in biological and synthetic systems, the properties and reactivity of C P Cu2 O2 species remain largely unexplored. Herein, we report the reversible interconversion of μ ‐1, 2‐ trans peroxido ( T P ) and C P dicopper cores. Ca II mediates this process by reversible binding at the Cu2 O2 core, highlighting the unique capability for metal‐ion binding events to stabilize novel reactive fragments and control O2 activation in biomimetic systems. Abstract : Calcium‐ion binding mediates the reversible interconversion of the prototypical trans ‐peroxido Cu2 O2 core ( T P ) to the rare and biologically relevant cis ‐peroxido Cu2 O2 core ( C P ). This provides new opportunities to stabilize novel reactive fragments and control O2 activation in biomimetic systems.